Drone fault tolerance strategy by allowing remaining rotor to pan and tilt - Zaludin, Zairil (Inderscience Publishers, 2024)
Quadcopter drones rely on their four rotors to control altitude and attitude. If one rotor fails, the drone loses its ability to maintain control. This paper proposes a solution to improve attitude control in such a scenario by minimising roll, pitch, and yaw deviations when a single rotor has stopped. By enabling opposing motors to pan and tilt independently, the study demonstrates the feasibility of landing the drone safely. The concept explores the idea of thrust vectoring by the individual rotor, which better manages the drone’s roll, pitch, and yaw angles, along with their respective rates. The paper includes simulation results and a summary of the performance improvements achieved through this approach. Copyright © 2024 Inderscience Enterprises Ltd.